Entrepreneurship education in Malaysia's public institutions of higher learning-A review of the current practices - Fakhrul Anwar, Zainol; Mohd Nor Hakimin, Yusoff; Mohamed Dahlan, Ibrahim (Canadian Center of Science and Education, 2015)
The need for a practical and applicable model for entrepreneurial learning is becoming critical. In this study, we aimed to collect data related to entrepreneurship education practices by all institutes of higher learning (IHLs) in Malaysia as well as challenges faced, facilities, and supports offered by the universities. Given the important role of IHLs to nurture and to create future entrepreneurs, the government via public IHLs aspires to produce “job creators” rather than “job seekers.” The findings of the study are significant as they provide practical insight into the entrepreneurship education practiced by the local public universities. In addition, the study also contributes to the present literature on the entrepreneurship education in Malaysia, particularly in presenting the practical issues and challenges faced by the universities in conducting entrepreneurship education programs.